A Heterobimetallic Superoxide Complex formed through O2 Activation between Chromium(II) and a Lithium Cation1. Issue 4 (4th December 2014) - Schax, Fabian; Suhr, Simon; Bill, Eckhard; Braun, Beatrice; Herwig, Christian; Limberg, Christian
Abstract The reaction of 1, 1, 3, 3‐tetraphenyl‐1, 3‐disiloxandiol (LH2) with n‐butyllithium and CrCl2 results in a mononuclear chromium(II) complex (1) that further reacts with O2 at low temperatures to yield a mononuclear chromium(III) superoxide complex [L2CrO2(THF)][Li2(THF)3] (2). The crystal structure revealed that the chromium superoxido entity is stabilized by the coordination to an adjacent lithium cation. Complex 2 thus contains an unprecedented heterobimetallic [CrIII(μ‐O2)Li+] core; beyond this it is the first chromium superoxide for which a temperature‐dependent magnetic characterization could be achieved, and the first structurally characterized representative with chromium in an exclusive O‐donor environment.